MENINGKATKAN KUALITAS PELAYANAN PUBLIK MELALUI PENGEMBANGAN BUDAYA KERJA - Endas Agjar1 (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2006)
The condition of public service delivery in Indonesia is so disappointing that it should be recovered immediately. Various malpractices can be found in any service institutions that expresses incapability of organization and employees in holding the delivery. Considering public service is the maintask of civil service, such awkwardness should be eliminated. The most strategic step to carry it out is by changing the service culture. Generally it is quite complicated to decide which service culture is the most appropriate to be applied as it will depend on the space, time, social condition, and organizational context. Therefore, the best approach to be used is contingency method, which is adaopting various service cultures with the situation. Any cultures`taken, the one should be put in mind is that the goal of public service delivery is to fulfil the needs of society.